The analysis of brain circulation of health care professionals in Serbia, Croatia and Slovenia - Milica Vasiljević Blagojević; Nevena Krasulja; Dejan Ilić; Dragan Milošević (BizInfo, 2023)
The deficiency of medical care professionals is a very popular economic and social problem that's becoming an important issue for a lot of countries. This paper aims to give an overall review and analysis of research results about the existence and reasons for migration (circulation) of highly educated healthcare personnel in Serbia, Croatia and Slovenia. The research that has been done in June 2022 included 604 students from three higher education institutions in Serbia, Croatia and Slovenia. The results, of which we came, showed that brain circulation happens mostly from economically weaker countries to the more developed ones, while better life standards, an opportunity for better studies and getting more practical skills are the most frequent motives for healthcare students.